Synthesis of reduced C, N-TiO2 for catalytic oxidation of HCHO indoors. Issue 13 (2nd July 2020) - Bao, Wen; Wang, Nan; He, Zhanhang
Abstract: Indoor HCHO pollution was becoming an issue with the increase of space confinement. In this article, C, N-TiO2 was prepared by the sol–gel method at low temperature and a series of r-C, N-TiO2 at different temperatures were synthesized under N2 . The materials were characterized by UV–Vis, FT-IR, PL, XRD, SEM, BET, and XPS. BET revealed the C, N-TiO2 had larger specific surface area than P25; XPS and PL illustrated the existence of surface oxygen vacancies and defects. The concentration of HCHO was determined by the phenol spectrophotometric method. The larger specific surface area and plentiful surface hydroxyl groups can effectively capture HCHO and O2 molecules; the surface oxygen vacancies and defects were conducive to generation of active oxygen species, which was benifit for the decomposition of HCHO. Among the prepared materials, r-C, N-TiO2 (400) has best catalytic oxidation activity for HCHO at room temperature and can reduce HCHO concentration to 0.06 mg/m 3 . This system was useful in gas purification with low production cost. Graphical abstract: